2004
DOI: 10.1051/alr:2004038
|View full text |Cite
|
Sign up to set email alerts
|

Changes in abundance and at-sea distribution of seabirds in the Bay of Biscay prior to, and following the “Erika” oil spill

Abstract: We investigated the impact of the "Erika" oil spill in the Bay of Biscay (France) on seabird populations. Relative abundance and spatial distribution at sea between 1980−1999 and 2000−2002 periods were compared. This study took place in a standardized monitoring at sea carried out with Coast Guard vessels following the line transect method. This work rests on 107 551 standardized counts of one minute before "Erika" and 23 449 after the oil spill. There was not a simple correlation between the number of individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
(10 reference statements)
1
9
0
Order By: Relevance
“…1 The study area in the south Bay of Biscay (north-east Atlantic, Europe) is delimited by the dotted line. Square grid indicates kilometres travelled during the whole study (see also Castège et al, 2004). detection of animals was made by naked eye, binoculars being used only for confirmation of the species and characteristics of the individuals.…”
Section: Modelling Animal Abundance: Cetaceans Seabirds and Fishesmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The study area in the south Bay of Biscay (north-east Atlantic, Europe) is delimited by the dotted line. Square grid indicates kilometres travelled during the whole study (see also Castège et al, 2004). detection of animals was made by naked eye, binoculars being used only for confirmation of the species and characteristics of the individuals.…”
Section: Modelling Animal Abundance: Cetaceans Seabirds and Fishesmentioning
confidence: 99%
“…Indeed, it should now be regarded as only one of the underlying causes as shown by Frederiksen et al (2004) who demonstrate that climate and fisheries together have caused the decline in North Sea Kittiwakes with an equal weighting given to these two factors. In the Bay of Biscay, this is also true for the successive oilspills such as the Erika (Castège et al, 2004) and more recently the Prestige, pollution events for which the real ecological impact assessment should be estimated in the more complex frame of natural population variations especially for large size mammals and seabirds characterized by a high generation time (Hémery et al, 2002). The consequence is that disentangling short term anthropogenic (such as oil spills) sources of variation from climate change may not be always easy (cf.…”
Section: Global Change Vs Human-borne Local Sources Of Variationmentioning
confidence: 99%
“…Transect sampling, such as line-transect and strip-transect surveys, has been used successfully to estimate density and abundance of marine mammals and marine birds around the world (Caretta et al 2001, Dawson et al 2004, Castège et al 2004, Gerrodette & Forcada 2005, Lowry & Forney 2005. However, only a few studies have used distance sampling methods to estimate marine turtle abundance or density at sea.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…We used data from the national long-term database , resulting from a standardised monitoring study of the at-sea abundance of seabirds and cetaceans using line transects (Buckland et al, 1993;Castège et al, 2004Castège et al, , 2007Hammond et al, 2002;Hémery et al, 1986;Seber, 1982;Skellam, 1958). The dataset has in total 131,000 min of observations (=2200 h total observation time), made from Coast Guard vessels (Douanes Françaises and the Affaires Maritimes).…”
Section: Cetacean Survey At Seamentioning
confidence: 99%
“…The study area in the south Bay of Biscay (north-east Atlantic, Europe) is delimited by the black dotted line. Square grid (sample units) in blue indicates kilometres travelled to measure cetacean encounter rate at sea during the whole study (see also Castège et al, 2004). Stranding network used in this study is shown in red.…”
Section: Fisheries Data and Fishing Indexmentioning
confidence: 99%